Violência contra crianças e adolescentes em Mato Grosso, 2013 a 2019 - Silva, Silvana Maria da (2021)
Violence presents itself as an important public health problem and there is nowhere in the world where it is absent. Regarding the violence perpetrated against children and adolescents as difficulties in the face of the diagnosis, they are even greater, since they happen mainly within the family, children and adolescents violated from intrafamily violence are more vulnerable to episodes of violence at school and in the community, that is are more susceptible in other microsystems. Furthermore, in Brazil, as networks of attention to violence are still poorly structured or inoperative. Objective: To analyze the reported cases of violence perpetrated against children and adolescents residing in Mato Grosso-Brazil, from 2013 to 2019. Methodology: A quantitative approach research was carried out, with an analytical descriptive design from a secondary database. The study population refers to cases of domestic violence, sexual and other interpersonal violence in children (0 to 9 years old) and adolescents (10 to 19 years old) residing in the state of Mato Grosso registered in the System for Violence and Accident Surveillance System Diseases Information System (VIVA-Sinan) from 2013 to 2019. The study variables according to the characteristics of the victim, the aggressor and the violence were subjected to descriptive statistical analysis and value through relative frequency . To assess the univariate and multivariate association between repetitive violence and independent variables, Odds ratios were estimated with their confidence intervals (95% CI) using logistic regression models. The trend analysis was used to verify the behavior of the completeness of the variables. Results: 5,742 cases of violence against children and adolescents were reported in the years 2013 to 2019 in the state of Mato Grosso, of which 71.3% were female. Adolescents (10-19 years) are the most affected (72.9%) when compared to children (68.0%). Regarding race / color, brown (62.2%) prevailed and there was a higher frequency of cases reported in elementary school (71.4%). The residence was the main place of occurrence of violence (65.1%), being higher in children (77.9%). Close people were the ones who most perpetrated the violence in both age groups. Except race / color, all of these factors were associated with the repetition of violence. As for completeness, 87 variables and 5,205 forms for reporting violence against children and adolescents were analyzed. There was the best completion (100.0%) for the variable 'gender of the victim' and the worst (58.0%) for the variable 'motivation of violence'. As for the degree of completeness, 26.4% of the variables had “excellent” completion, 59.8% “good”, 10.3% “bad” and 3.5% “regular”. In the set of variables, completeness showed an increasing trend (75%). Conclusion: The study offers relevant information on violence against children and adolescents, highlighting the factors associated with the repetition of violence, in Mato Grosso, contributing to expand scientific knowledge on the subject and support coping actions.